Country Partnership Framework for the Republic of Sierra Leone for the Period FY21 - FY26 - World Bank; International Finance Corporation; Multilateral Investment Guarantee Agency (World Bank, Washington, DC, 2020)
Sierra Leone has an advantageous geography and abundant mineral, agricultural and blue resources, yet the country’s per capita gross domestic product (GDP) is almost the same as it was after independence. This CPF is highly selective and opportunistic, focusing on putting the fundamentals in place, with a strong emphasis on critical development accelerators that touch the lives of every Sierra Leonean: human capital, energy and technology.